2017
DOI: 10.14260/jemds/2017/354
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Management of Lower Limb Varicose Veins

Abstract: BACKGROUNDThe first written reference of varicose veins appears to be the Ebers Papyrus dated 1550 B.C. It is one of the oldest documented pathological conditions in existence today. This study deals with its aetiology, pathology and the different modes of treatment and their efficacy in detail. MATERIALS AND METHODS50 patients with lower limb varicose veins admitted in the Department of General Surgery, KIMS, Karad from October 2014 to July 2016 were included in the study. All patients were subjected to detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…15 The present study noted long saphenous vein involvement in most 18 (85.7%) of the cases followed by both long and short saphenous vein involvement in 3 (14.28%). These observations are in accordance with the findings of Janugade et al and Naik et al 9,16 In this present study 95.23% of patients had perforator incompetence. Which shows that majority of the cases presenting to hospital for treatment are advanced cases of hemodynamic disturbances of the limb and it is compared with study conducted by Donnell et al where 79.48% of patients had perforator in competence.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…15 The present study noted long saphenous vein involvement in most 18 (85.7%) of the cases followed by both long and short saphenous vein involvement in 3 (14.28%). These observations are in accordance with the findings of Janugade et al and Naik et al 9,16 In this present study 95.23% of patients had perforator incompetence. Which shows that majority of the cases presenting to hospital for treatment are advanced cases of hemodynamic disturbances of the limb and it is compared with study conducted by Donnell et al where 79.48% of patients had perforator in competence.…”
Section: Discussionsupporting
confidence: 94%
“…By definition they are dilated, elongated and tortuous veins.8 In the present study, the higher incidence of varicose veins was observed between the age group 20-40 years which correlates well with the studies of Janugade et al and Vaidyanathan et al 9,10 Males 20 (95.3%) are commonly affected than females in this study. Similar observations were seen in the studies of Nagaraj et al 11 This variation might due to the factor that cosmesis is not concern for low and middle-class women in our country, only complications associated with the disease makes the patient to consult the doctor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The era of vascular intervention for varicose veins was modernized by Friedrich Trendelenburg, in the 1860s, who not only popularized his eponymous Trendelenburg test for saphenous reflux but also performed great saphenous vein (GSV) ligation by making a transverse upper thigh incision to ligate and divide the proximal GSV [1]. William Moore, an Australian surgeon, moved the site of ligation cephalad to the sapheno-femoral junction [1]. Ligation of the saphenofemoral junction as it is practiced today was first described by John Homans in his paper in 1916 [1].…”
Section: Historymentioning
confidence: 99%
“…Varicose veins constitute a progressive disease, and remission of the disease does not occur, except after pregnancy and delivery. During its course, the disease produces complication; most frequent are superficial thrombophlebitis, acute bleeding originating in one of the thin-walled varices, eczema, and, finally, skin ulceration [1].…”
Section: Introductionmentioning
confidence: 99%